2012
DOI: 10.1182/blood-2011-09-380568
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical absence of a prothrombotic phenotype in a mouse model of severe hyperhomocysteinemia

Abstract: Hyperhomocysteinemia confers a high risk for thrombotic vascular events, but homocysteine-lowering therapies have been ineffective in reducing the incidence of secondary vascular outcomes, raising questions regarding the role of homocysteine as a mediator of cardiovascular disease. Therefore, to determine the contribution of elevated homocysteine to thrombosis susceptibility, we studied Cbs ؊/؊ mice conditionally expressing a zinc-inducible mutated human CBS (I278T) transgene. Tg-I278T Cbs ؊/؊ mice exhibited s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 42 publications
4
29
1
1
Order By: Relevance
“…However, CBS deficiency did not result in a prothrombotic phenotype. In fact the CBS-null animals displayed normal rates of fibrinolysis [59]. Since these authors were unable to reproduce the findings of the Hajjar study [57,60], they speculated that the prothrombotic phenotype observed in diet-induced hyperhomocysteinemia might not be due to elevated homocysteine but possibly due to other dietary metabolites.…”
Section: Role Of the P36 2 /P11 2 Complex In Hyperhomocysteinemiacontrasting
confidence: 41%
“…However, CBS deficiency did not result in a prothrombotic phenotype. In fact the CBS-null animals displayed normal rates of fibrinolysis [59]. Since these authors were unable to reproduce the findings of the Hajjar study [57,60], they speculated that the prothrombotic phenotype observed in diet-induced hyperhomocysteinemia might not be due to elevated homocysteine but possibly due to other dietary metabolites.…”
Section: Role Of the P36 2 /P11 2 Complex In Hyperhomocysteinemiacontrasting
confidence: 41%
“…However, it has been reported to have decreased clotting times in a tail bleeding assay and that this effect is reversible by short-term betaine treatment. No differences in clotting behavior have been observed in Tg-I278T Cbs −/− mice (Gupta et al 2009; Dayal et al 2012). It is unclear why the two models behave so differently, although strain background differences are a distinct possibility.…”
Section: Discussionmentioning
confidence: 94%
“…Susceptibility to thrombosis in the venous system was measured as described previously (72). Briefly, mice were anesthetized with ketamine/xylazine (87.5 mg/kg ketamine and 12.5 mg/kg xylazine i.p.).…”
Section: Methodsmentioning
confidence: 99%